1993
DOI: 10.1177/019459989310900307
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial infections of the head and neck

Abstract: Despite the decline of pulmonary tuberculosis in the Western world, the incidence of cervical mycobacterial infections has remained relatively unaffected. A retrospective review was conducted of 20 patients treated for head and neck tuberculosis from 1984 to 1991. They were mostly an immigrant group coming from underdeveloped countries close to the equator. All cases were treated with antituberculous chemotherapy; 18 patients also underwent surgical excision of their lymphadenopathy. Sixteen patients showed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 17 publications
5
26
1
Order By: Relevance
“…A single enlarged cervical lymph node was the most common presentation, with symptoms localized to the involved lymph node site. This has been well described in the literature (5)(6)(7)(19)(20)(21)(22)(23).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…A single enlarged cervical lymph node was the most common presentation, with symptoms localized to the involved lymph node site. This has been well described in the literature (5)(6)(7)(19)(20)(21)(22)(23).…”
Section: Discussionsupporting
confidence: 66%
“…While other studies have focused on peripheral TBL disease alone, this study included cases of TBL with a site of active TB elsewhere (6,20,21). We found 18% of our TBL cases with active TB documented elsewhere, both in HIV-infected and uninfected individuals (22).…”
Section: Discussionmentioning
confidence: 99%
“…The most common site of lymph node enlargement in order of occurrence is the neck (cervical), axilla, inguinal and submandibula. 10,13,19 This finding did not differ from the previous study. We found that in both groups, lymph node enlargement mostly occurred in the neck (44% and 60% respectively) and submandibula (16% and 23% respectively).…”
Section: Discussioncontrasting
confidence: 50%
“…[10][11][12] Enlargement of the lymph nodes outside the cervical area indicates a serious form of TB with systemic process. 7,13 Another opinion stated that multiple process is frequently found in the enlargement of superficial lymph nodes caused by MTB. 7,11,14 The aim of this study was to investigate the clinical aspects and result of Mantoux test in superficial lymphadenitis caused by Mycobacterium tuberculosis compared to that caused by non-tuberculosis organism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation